Differences in antimicrobial susceptibility testing complicating management of IMP carbapenemase-producing Enterobacterales infection. (December 2021) - Hickey, C.; Nguyen, S.; Anes, J.; Hurley, D.; Donoghue, O.; Fanning, S.; Schaffer, K.
Highlights: Overreporting of meropenem resistance by VITEK® 2 in IMP-CPE isolates. Whole-genome sequencing analysis of IMP-CPE isolates. Antibiotic treatment of severe sepsis caused by IMP-CPE isolates. ABSTRACT: Objectives: IMP-type carbapenemases are rarely detected in Europe and limited information is available to guide the treatment of infections caused by carbapenemase-producing Enterobacterales (CPE) producing these carbapenemases. Accurate antimicrobial susceptibility testing (AST) results are essential for optimal antibiotic management. Here we report discrepancies in AST of IMP-producing Enterobacterales (IMP-CPE) complicating the management of severe sepsis. Methods: Antimicrobial susceptibilities were analysed by in-house VITEK® 2, Etest and broth microdilution (BMD). Carbapenemase-encoding genes were detected by PCR. Whole-genome sequencing (WGS) was performed using an Illumina MiSeq platform. Results: Minimum inhibitory concentrations (MICs) determined by VITEK® 2 for Enterobacter hormaechei and Klebsiella oxytoca blood culture isolates were ≥16 mg/L for meropenem and ≤0.5 mg/L for ertapenem. In contrast, Etest analysis and BMD returned MICs of 2 mg/L and 1 mg/L, respectively. Both isolates tested positive for IMP carbapenemase-encoding genes by PCR. WGS revealed that both isolates carried the same bla IMP-4 gene. Based on VITEK® 2 susceptibilities, initial treatment was with tigecycline and amikacin. After subsequent deterioration, the patient was successfully treated with ertapenem and amikacin. Conclusion: This case highlights that automated AST by VITEK® 2 can over-report meropenem resistance for IMP carbapenemase-producers compared with Etest and BMD. Clinicians need to be cautious deciding against carbapenem treatment based on VITEK® 2 susceptibility testing results for IMP-positive Enterobacterales. Tigecycline was inferior to carbapenem treatment for pyelonephritis caused by isolates expressing IMP carbapenemases, however specific evidence guiding the treatment of these infections is lacking.